2005
DOI: 10.1111/j.1600-079x.2005.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin reduces pancreatic prostaglandins production and protects against caerulein‐induced pancreatitis in rats

Abstract: Melatonin has been used to treat experimental pancreatitis, although not all the drug's therapeutic mechanisms of melatonin have been defined. Prostaglandins (PGs) are proinflammatory mediators that exert their effects mainly locally during inflammatory diseases. The present study was undertaken to examine whether treatment with melatonin influences local PG production. An acute pancreatitis model in male Sprague-Dawley rats (225-275 g) was established by continuously infusing caerulein (15 mg/kg/hr). Mean art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 26 publications
(27 reference statements)
1
19
0
Order By: Relevance
“…Previous experimental studies have shown that pretreatment with melatonin could prevent pancreatic inflammation and radically reduce pancreatic tissue damage in rats subjected to acute pancreatitis in different experimental models [13,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73]. This was evidenced by histological assessment of pancreatic tissue and prominent decline of the inflammatory markers, such as edema, neutrophil infiltration, and vacuolization of the acinar cells [60,61,62,63,73].…”
Section: Melatonin System and Acute Pancreatitismentioning
confidence: 99%
See 3 more Smart Citations
“…Previous experimental studies have shown that pretreatment with melatonin could prevent pancreatic inflammation and radically reduce pancreatic tissue damage in rats subjected to acute pancreatitis in different experimental models [13,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73]. This was evidenced by histological assessment of pancreatic tissue and prominent decline of the inflammatory markers, such as edema, neutrophil infiltration, and vacuolization of the acinar cells [60,61,62,63,73].…”
Section: Melatonin System and Acute Pancreatitismentioning
confidence: 99%
“…This was evidenced by histological assessment of pancreatic tissue and prominent decline of the inflammatory markers, such as edema, neutrophil infiltration, and vacuolization of the acinar cells [60,61,62,63,73]. In animals with acute pancreatitis pretreated with melatonin, there was a significant reduction in the plasma morphometric indicators of pancreatic inflammation severity, blood levels of the enzymes, amylase and lipase, and blood levels of pro-inflammatory cytokines (e.g., TNFα, IL-1β, and IL-6), whereas anti-inflammatory interleukins IL-10 and IL-4 were increased [10,59,62,63,64,65,66,67,68,69,70]. The antioxidant effect of melatonin was expressed as a reduction of lipid peroxidation products (MDA + 4-HNE) in the pancreas and was accompanied by increased activity of antioxidant enzymes SOD, CAT, GPx, and GSH [62,63,64,65,66,67,69,70].…”
Section: Melatonin System and Acute Pancreatitismentioning
confidence: 99%
See 2 more Smart Citations
“…Melatonin exerts its beneficial effects through several mechanisms, including scavenging free radicals, activating antioxidative enzymes, inhibiting neutrophil infiltration, promoting neutrophil apoptosis, modulating cytokine production and altering the generation of pancreatic prostaglandins [10,11,18,22,30,46,50]. In addition, the melatonin precursor, L-tryptophan, increases the level of melatonin in the blood and attenuates AP in rats [22,26,50].…”
Section: Discussionmentioning
confidence: 99%